Comparison of the Effects of Cold Compress and Xyla-P Cream on Stress Caused by Venipuncture among Hemodialysis Patients - Ghoreyshi 1, Ziba; Amerian 2, Monireh; Amanpour 3, Farzaneh; Ebrahimi 4*, Hossein (Shahroud Journal of Medical Sciences, 2018)
Background: Stress caused by the insertion of the needle into the arteriovenous fistula is one of the main concerns of hemodialysis patients. Reducing the stress of patients during venipuncture is one of the main goals of nursing care.This study aimed to investigate and compare the effects of Xyla-P cream and cold compress on the severity of stress caused by venipuncture in hemodialysis patients.Methods: This clinical trial was conducted in 50 patients Undergoing hemodialysis who were enrolled in the study using simple random sampling.The severity of stress was measured during two successivehemodialysis sessions in three stages including after the application of a placebo, Xyla-P cream, and cold compress. The visual analog scale was used to measure the severity of stress. The data collector and data analyzer were blinded. The collected data were analyzed using analysis of variance with repeated measures.Results: The stress scores were significantly different between the placebo group (6.69±1.66)and Xyla-P cream group (5.43±1.42)(P=0.000) and cold compress group (5.05±1.40)(P=0.000), and between Xyla-P cream group and cold compress group (P=0.026). Conclusions: Cold compress is more effective than Xyla-P cream in reducing the stress. Therefore, nurses are recommended to use this method, instead of medications, for reducing the stress.Conclusions: Cold compress is more effective than Xyla-P cream in reducing the stress. Therefore, nurses are recommended to use this method, instead of medications, for reducing the stress.